Neonatal Outcomes of Triplet Pregnancies Conceived via In Vitro Fertilization versus Other Methods of Conception - Badreldin, Nevert; Peress, Danielle A.; Yee, Lynn M.; Battarbee, Ashley N. (American Journal of Perinatology, 2020)
Objective This study aims to investigate neonatal outcomes of triplet gestations conceived via in vitro fertilization (IVF) compared with those not conceived by IVF.Study Design This is a retrospective cohort study of women who delivered a triplet gestation ≥24 weeks at a large academic center (2005–2016). Women with unknown mode of conception were excluded. Women who conceived via IVF were compared with those conceiving spontaneously or through non-IVF fertility treatments. The primary outcome was a composite severe neonatal morbidity (respiratory distress syndrome, necrotizing enterocolitis, severe intraventricular hemorrhage, retinopathy of prematurity, neonatal sepsis, or death). Bivariate comparisons were made by mode of conception and unadjusted generalized estimating equations were used to estimate odds ratios (OR) after accounting for the clustering of neonate by mother.Results Among 82 women included in this analysis, 51 (62%) conceived via IVF. Women who conceived via IVF were older (35.2 vs. 30.7, p < 0.001) and more likely to be of non-Hispanic white race/ethnicity (91.8 vs. 70.0%, p < 0.01) and married (100 vs. 90.0%, p = 0.02) when compared with women who did not conceive via IVF. Although women who conceived via IVF delivered at an earlier gestational age than those who did not (32.9 ± 3.0 vs. 33.7 ± 2.6 weeks, p = 0.02), there was no significant difference in composite neonatal morbidity (34.0 vs. 28.0%, p = 0.32; OR: 1.33, 95% CI: 0.60–2.91). Additionally, there were no significant differences between the groups with regard to other neonatal outcomes examined, including fetal growth restriction, birthweight, umbilical artery pH <7, neonatal intensive care unit admissions, duration in the NICU, need for mechanical ventilation, or duration of mechanical ventilation.Conclusion Neonatal outcomes among triplet gestations did not differ by IVF in this well-characterized, single-center cohort.
Keywords: in vitro fertilization; morbidity; neonatal; pregnancy; preterm birth; triplet